2022
DOI: 10.1055/s-0042-1750749
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty for Osteoarthritis Is Uncommon after Intralesional Curettage in Giant Cell Tumor of Bone

Abstract: Giant cell tumor of bone (GCTB) is most often treated with intralesional curettage; however, periarticular lesions have been shown to increase risk for osteoarthritis. Additionally, the location of these lesions may occasionally preclude a joint-sparing procedure in recurrent tumors. This study sought to investigate rates of secondary arthroplasty in long-term follow-up of knee GCTB. Cases of knee GCTB treated at our institution were reviewed. Rates of recurrence and secondary arthroplasty were recorded, and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Lee et al [18] had six joint replacements in 40 patients with GCTB treated with intralesional curettage, and reported that arthroplasty was performed as a secondary procedure in patients with GCTB at a relatively infrequent rate and more often for cases of recurrent disease than for osteoarthritis. Wechsler et al [4] reported that 1 out of 14 patients had a joint replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [18] had six joint replacements in 40 patients with GCTB treated with intralesional curettage, and reported that arthroplasty was performed as a secondary procedure in patients with GCTB at a relatively infrequent rate and more often for cases of recurrent disease than for osteoarthritis. Wechsler et al [4] reported that 1 out of 14 patients had a joint replacement.…”
Section: Discussionmentioning
confidence: 99%